PENGELOLAAN TERMINAL BANDAR RAYA PAYUNG SEKAKI OLEH UNIT PELAKSANA TEKNIS DINAS (UPTD) TERMINAL DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMASI KOTA PEKANBARU - Gultom, Christian B. A; R. F. S, Harapan Tua (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Management of terminal Bandar Raya Payung Sekaki Pekanbaru city conducted by UPTD Terminal under the control of Departement of Transportation, Communications and Information. Terminal Bandar Raya Payung Sekaki start operating in 2006. This terminal is classified as a terminal Type A that is equipped with facilities that are very complete. But in terms operating until recently, terminal Bandar Raya Payung Sekaki not run according to purpose. From the observations made there are still many problem such as the still low level of public participation and lack of supervision cause the failure in the management of terminal.The purpose of this research is to see how the management terminal Bandar Raya Payung sekaki by UPTD Teminal Department Transportation Communication and Information Pekanbaru city and factors affecting management terminal Bandar Raya Payung Sekaki by UPTD Terminal Department Transportation Communication and Information city pekanbaru. To analyze phenomena in this research the writer is used theory George R.Terry with an indicator attainment success seen from planning , organizing, actuating and controlling. As for looking at factors that affect the management of terminal based on the research in field. The results showed management terminal Bandar raya Payung Sekaki by UPTD Terminal Department of Transportation Communication and Information have not run well.The factors which found is human resources, the lack of the rule of law and public participation.Keywords: Organitation, Management of Terminal, Operating